ACT-26 ABT-414 (DEPATUX-M) IN NEWLY DIAGNOSED AND RECURRENT GLIOBLASTOMA: WHERE DO WE STAND?. (16th December 2019) - Preusser, Matthias
Abstract: Epithelial growth factor receptor (EGFR) amplifications are found in approximately half of glioblastoma cases and targeting of the EGFR axis is an attractive treatment paradigm in this tumor type. However, several anti-EGFR drugs have failed to achieve significant and meaningful improvements in clincial trials. ABT-414 (Depatux-M) is an antibody-drug conjugate (ADC) that combines a cytotoxic agent with an antibody targeting EGFR, thus aiming at specific tummor cell killing through intracellular toxin delivery. The activity of ABT-414 has been evaluated in two large clinical trials enrolling glioblastoma patients. Intellance-2 enrolled 260 patients with first recurrence of EGFR-amplified glioblasoma into a chemotherapy control arm (temozolomide or lomustine) or one of two experimental arms (ABT-414 monotherapy or ABT-414 combined with temozolomide). Depatux-M in combination with temozolomide showed a trend towards improved survival times compared to temozolomide/lomustine alone, with patients relapsing more than 4 months after the last adjuvant temozolomide cycle deriving the greatest benefit. Intellance-1 was a randomized, placebo-controlled Phase 3 study and was designed to evaluate the efficacy and safety of Depatux-M versus placebo when administered with concurrent radiation and temozolomide and with adjuvant temozolomide in subjects with newly diagnosed EGFR-amplified glioblastoma. The primary endpoint was overall survival. Recently, it was announced that a preplaned interim analysis based on data from 639 patients showed the lack of a survival benefit for patients exposed to Depatux-M. In summary, the currently available data do not support routine use of Depatux-M in glioblastoma patients and further studies are needed to understand resistance mechanisms limiting therapeutic efficacy of EGFR-targeting in glioblastoma.